Ability of Ornamental Plants in Adsorbing Dust from Vehicles (Case Study: Bumi Serpong Damai) - Sobri Effendy; Nadita Zairina Suchesdian; Ibnul Qayim (Agromet, 2017)
This research measured several vegetations that were planted in Bumi Serpong Damai, South Tangerang to absorb dust pollutions produced by vehicles. The locations for monitoring were divided based on traffic levels: high, medium and low. We measured the pollution based on two approaches i.e. measuring every four hours and a daily measurement. Based on our monitoring, each species will have different feedbacks to dust pollution at various traffic conditions. We found that species of Heliconia was able to absorb the dust at the top for high traffic condition, whereas Kaca Piring is effective for medium traffic. Our findings revealed that monitoring dust should be frequent at least four hours/day, and selection of species for reducing dust pollution should consider the leave structure.